THE ESSENCE AND NECESSITY OF INTRODUCING DIGITAL TECHNOLOGIES IN THE DEVELOPMENT OF HUMAN CAPITAL - Saparbaeva Dilfuza Bakhtiyarovna (American Journals Publishing, 2024)
The article is devoted to the essence and necessity of the introduction of digital technologies in the development of human capital, and the literature of economists was studied as part of the research. Also, the main directions of human capital development were investigated and a conclusion was formed at the end.
Keywords: Capital, digital technology, human capital, technological determinism